Clinical associations with uterine tachysystole. (April 2014) - Smith, Samuel; Zacharias, Judy; Lucas, Vicki; Warrick, Philip A.; Hamilton, Emily F.
Abstract Objectives: To determine the incidence of uterine tachysystole (UT) and its association with neonatal depression or metabolic acidemia (DEP). Methods: This retrospective study comprised all 6234 women at ≥37 weeks' gestation who were monitored during the last 4 hours of tracings before birth in an academic community hospital. DEP was defined by an umbilical artery base deficit value ≥10 mmol/L or a 5-minute Apgar ≤6 and included 77 births. UT was defined by >15 contractions in 30 minutes. Results: The overall incidence of UT was 18.3% (1139/6234). In 4.2% (260/6234) UT persisted for >60 min. The rate of UT was similar in births with DEP (14.3%, 11/77) compared to those without DEP (18.3%, 1128/6157; p = 0.45). In births with UT, only 1.0% (11/1139) developed DEP. The DEP group had more decelerations at almost every level of contractions and a higher cesarean rate of 49.4% (38/77) compared to 24.0% (1468/6124); p = <0.001 in the group without DEP. Conclusions: UT was common, occasionally prolonged and almost always benign. Fetuses with DEP had no more UT than those without DEP. Many babies with DEP declared their vulnerability with decelerations at contraction rates below UT levels and the great majority of them never experienced UT.